Home stimulation, development, and nutritional status of children under 2 years of age in the highlands of Madagascar - Hasina Rakotomanana; Deana Hildebrand; Gail E. Gates; David G. Thomas; Fanjaniaina Fawbush; Barbara J. Stoecker (BMC, 2023)
Abstract Background The Vakinankaratra region of Madagascar has a high burden of child undernutrition which, in addition to poor psychosocial stimulation, is a strong risk factor of poor child development. However, there are limited studies evaluating the relations between developmental deficits, child nutrition outcomes, and home stimulation in the region. The purpose of this study was to assess the development of children aged 11-13 months in relation to their nutritional status and to examine parental home stimulation attitudes and practices in the Vakinankaratra region. Methods Cognitive (n = 36), language (n = 36), motor (n = 36), and socioemotional (n = 76) development were assessed using the Bayley Scales of Infant and Toddler Development III. Household stimulation environment was evaluated using the family care indicators survey. Stunting (length-for-age z-score < − 2) and underweight (weight-for-age z-score < − 2) were determined using the 2006 WHO growth standards. Perceptions of and barriers to greater home stimulation for children were collected using focus group discussions among parents and in-depth interviews with community nutrition agents. Results Almost all mothers reported that parent-child interaction with talk and play was very important. Alarmingly high stunting rates (> 69%) were observed in this subsample. Limited time and tiredness were the major barriers to home stimulation mentioned by parents and confirmed by key informants. Children had a very limited variety of play materials, and most of the mothers used household objects (75%) and materials from outside the house (71%) as children's toys. Composite cognitive [mean (SD): 60 (10.3)], motor [61.9 (13.4)], language [62 (13.2)], and socioemotional [85.1 (17.9]) scores were low. Fine motor, cognitive, and receptive and expressive language scores were correlated [0.4 < r < 0.7, p < 0.05]. Conclusions The very high stunting rates and very low performance on cognitive, motor, language, and socioemotional development assessments of children in the Vakinankaratra region require urgent attention.